Planning Consistency Analysis and Palopo City Government Budgeting Year 2016 -2020 - A. Dahri Adi Patra; Andika Rusli (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This study aims to determine the level of consistency of the regional medium-term program plan (RPJMD) with the local government work plan (RKPD) as a planning document and the consistency of the RKPD and APBD as budget documents as well as the ability of local governments to implement programs and activities listed in the APBD which are designed with a qualitative discriptive research approach using a model  Planning and budgeting consolidation matrix (MKPP) with  a framework analysis technique of relationships or linkages between planning documents and regional budgeting documents expressed in the form of percentage of linkage with categories: very bad (0 - 19.9%), bad (20% - 39.9%), medium (40% - 59.9%), good (60% - 79.9%) and very good (80% - 100%).  The results of this study show that the level of consistency of the RPJMD and RKPD documents of the  Palopo City Government within a period of 5 years (2016 -2020) averaged 93.60% or classified as very good, as well as the consistent level between the RKPD and APBD reached an average of 88.58% or classified as very good. Similarly, the level of the government's ability to implement activity programs reached 99.4% with the very good category, and the ability to carry out activities reached 99.1% with the very good category.